2019
DOI: 10.1371/journal.pone.0222682
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for the cervical spinal canal and the vertebral bodies by MRI in a general population

Abstract: PurposeTo provide population-based reference values for cervical spinal canal parameters and vertebral body (VB) width and to study their associations with sex, age, body height, body weight and body mass index (BMI) using MRI.MethodsCross-sectional analyses included data from 2,453 participants, aged 21–89 years, of the population-based Study of Health in Pomerania (SHIP) who underwent whole-body MRI at 1.5 Tesla between July 2008 and March 2011. A standardised reading was performed for the C2-C7 cervical spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Nell et al measured normal values for the spinal canal in 2.453 subjects. Neither sex nor body weight or BMI had a significant influence on the width of the spinal canal [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nell et al measured normal values for the spinal canal in 2.453 subjects. Neither sex nor body weight or BMI had a significant influence on the width of the spinal canal [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although all subjects were healthy, some had minor pathological and clinical problems, which might have affected the findings. Due to the excellent intra- and interobserver reproducibility of MRI measurements, measurements were performed only once by a single observer [ 28 ]. These objective measurements were carried out by an experienced radiology technician with an excellent knowledge of the human anatomy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have reported that height may affect spinal morphometric measurements. [9,18] Future studies using anthropometric measurement information can provide useful information on this subject. Second, intra-and inter-observer variability could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%